Excellence in the stacks : strategies, practices and reflections of award-winning libraries - Hill, Jacob; Swords Steffen, Susan; ScienceDirect eBooks (Oxford, UK : Chandos Publishing, 2013)
Excellence in the Stacks details the philosophies, practices and innovations of award-winning libraries over the last ten years. It will inform the profession and highlight the themes and strategies these liberal-arts colleges share, and where they differ. Using the Association of Research and College Libraries Excellence in Academic Libraries Award standards as guidelines for exploring librarianship, this book gathers the perspectives of all types of librarians at all levels of employment. By highlighting winners' holistic approaches it helps define and focus the energies of college libraries in their pursuit of outstanding service and increased valuation by their parent institution.
Measuring the excellence of librarianship at Earlham College / Neal Baker and Nancy Taylor -- Graduate services at the Newman Library / Linda Rath and Christopher Tuthill -- The evolving liaison model at Mount Holyoke College / Alex Wirth-Cauchon -- Fast-forward: the transformation of excellence / Carla B. Tracy -- In unison with our communities and with each other: striving for excellence in college librarianship / Sam Demas -- Looking outward: partnerships and outreach at Hollins University / Luke Vilelle and Maryke Barber -- The A.C. Buehler Library at Elmhurst College: handcrafted academic library services / Peg Cook, Donna Goodwyn, Jacob Hill, Elaine Fetyko Page, Jennifer Paliatka, Susan Swords Steffen -- Success through community: engagement at Grinnell College Libraries / Julia Bauder and Beth Bohstedt -- Excellence at Champlain: spending Groundhog Day in the Kuhlthau model / Janet R. Cottrell -- Afterword: academic library value and the college library / Susan Swords Steffen.
Includes bibliographical references and index.
Jacob Hill is the reference and instruction librarian for the award-winning A.C. Buehler Library at Elmhurst College. He has recently presented and published content on plagiarism-detection software, mobile resource access, and reference desk communication applications. Jacob is currently investigating college/secondary education liaison program partnerships. Susan Swords Steffen is the director of the library at Elmhurst College in Elmhurst, Illinois. With over 30 years of experience in college libraries, she has spoken and written extensively about library innovation and has taught at the Graduate School of Library and Information Science at Dominican University as an adjunct faculty member.
Print version record.
Elsevier
Safari Books Online
Keywords: Libraries; Academic libraries -- Relations with faculty and curriculum; Library outreach programs; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Academic libraries -- Relations with faculty and curriculum; Libraries; Library outreach programs; Library Services -- trends; Library Management; Library policy and strategy; Library leadership and general management; Electronic books